From informational reading to information literacy: Change and continuity in document work in Swedish schools - Hampson Lundh, Anna; Dolatkhah, M.; Limberg, L. (Emerald Group Publishing Limited, 2018)
© 2018, Emerald Publishing Limited. Purpose: The purpose of this paper is to historicise research conducted in the fields of Information Seeking and Learning and Information Literacy and thereby begin to outline a description of the history of information in the context of Swedish compulsory education. Design/methodology/approach: Document work and documentary practices are used as alternatives to concepts such as information seeking or information behaviour. Four empirical examples of document work – more specifically informational reading – recorded in Swedish primary classrooms in the 1960s are presented. Findings: In the recordings, the reading style students use is similar to informational reading in contemporary educational settings: it is fragmentary, facts-oriented, and procedure-oriented. The practice of finding correct answers, rather than analysing and discussing the contents of a text seems to continue from lessons organised around print textbooks in the 1960s to the inquiry-based and digital teaching of today. Originality/value: The paper seeks to analyse document work and documentary practices by regarding “information” as a discursive construction in a particular era with material consequences in particular contexts, rather than as a theoretical and analytical concept. It also problematises the notion that new digital technologies for producing, organising, finding, using, and disseminating documents have drastically changed people’s behaviours and practices in educational and other contexts.